Penerapan metode role playing untuk meningkatkan pemahaman materi upaya bangsa indonesia dalam mempertahankan kedaulatannya pada siswa kelas v sekolah dasar - Revina Fatith Hidayatika; Hasan Mahfud; Supianto Supianto (Universitas Sebelas Maret, 2023)
Abstract. Social studies is one of the subjects that is difficult for fifth-grade students to understand at Banyurip 2 Public Elementary School. Using appropriate learning methods will make teaching and learning activities easier for teachers and students. The role-playing learning method is felt to help teachers convey historical material and make it easier for students to understand the material. The research approach used qualitative research with a classroom action research method which was carried out collaboratively with the fifth-grade teachers at Banyurip 2 Public Elementary School. The research subjects were all fifth-grade students at Banyurip 2 Public Elementary School for the 2022/2023 academic year. Data collection techniques include observation, interviews, documentation, and tests. Data validity testing techniques used method triangulation and data source triangulation, as well as data analysis techniques based on Miles and Huberman. The results of research that has been conducted on fifth-grade students of Banyurip 2 Public Elementary School show that the use of role-playing learning methods can increase understanding. Evidenced by the increased learning outcomes after the action using the role-playing method, as well as based on observations that have been made during the action.Keywords: Social Science, historical material, role-playing method.